2017
DOI: 10.4274/mirt.70894
|View full text |Cite
|
Sign up to set email alerts
|

A Family with Von Hippel-Lindau Syndrome: The Findings of Indium-111 Somatostatin Receptor Scintigraphy, Iodine-123 Metaiodobenzylguanidine Scintigraphy and Single Photon Emission Computerized Tomography

Abstract: Von Hippel-Lindau syndrome (VHLS) is an autosomal dominant hereditary familial disorder characterized by development of malignant and benign neoplasms. Differential diagnosis of the adrenal and pancreatic masses are difficult in patients with VHLS. Iodine-123 metaiodobenzylguanidine (I-123 MIBG) and indium-111 somatostatin receptor scintigraphies (In-111 SRS) have important roles in the differential diagnosis of adrenal and pancreatic masses in those patients. In this case report, we present the findings of I-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Most of these studies were conducted in Europe ( n =18) ( 16 , 17 , 21 , 25 , 26 , 28 , 29 , 62 , 66 , 68 , 70 , 71 , 72 , 73 , 76 , 83 , 91 , 92 ), followed by Eastern Asia ( n =17) ( 35 , 36 , 40 , 44 , 45 , 47 , 48 , 74 , 75 , 77 , 78 , 79 , 80 , 81 , 82 , 86 , 87 ) and North America ( n =9) ( 53 , 59 , 60 , 61 , 63 , 64 , 65 , 69 , 84 ). All studies assessed patients of all age groups, with the mean onset age of PPGL being 28.8 years (as reported in 21 studies ( 21 , 26 , 35 , 40 , 44 , 47 , 55 , 59 , 60 , 61 , 65 , 67 , 71 , 72 , 74 , 77 , 79 , 85 , 86 , 87 , 88 )). Six studies reported a cons...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of these studies were conducted in Europe ( n =18) ( 16 , 17 , 21 , 25 , 26 , 28 , 29 , 62 , 66 , 68 , 70 , 71 , 72 , 73 , 76 , 83 , 91 , 92 ), followed by Eastern Asia ( n =17) ( 35 , 36 , 40 , 44 , 45 , 47 , 48 , 74 , 75 , 77 , 78 , 79 , 80 , 81 , 82 , 86 , 87 ) and North America ( n =9) ( 53 , 59 , 60 , 61 , 63 , 64 , 65 , 69 , 84 ). All studies assessed patients of all age groups, with the mean onset age of PPGL being 28.8 years (as reported in 21 studies ( 21 , 26 , 35 , 40 , 44 , 47 , 55 , 59 , 60 , 61 , 65 , 67 , 71 , 72 , 74 , 77 , 79 , 85 , 86 , 87 , 88 )). Six studies reported a cons...…”
Section: Resultsmentioning
confidence: 99%
“…All studies assessed patients of all age groups, with the mean onset age of PPGL being 28.8 years (as reported in 21 studies ( 21 , 26 , 35 , 40 , 44 , 47 , 55 , 59 , 60 , 61 , 65 , 67 , 71 , 72 , 74 , 77 , 79 , 85 , 86 , 87 , 88 )). Six studies reported a consecutive sample ( 16 , 17 , 29 , 66 , 77 , 78 ), whereas in 39 studies a convenience sample was assessed ( 21 , 25 , 35 , 45 , 47 , 53 , 56 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations